Penerapan Model Pembelajaran Experiential Learning Dalam Pendidikan KewirausahaanDi Sma Serba Bakti - Haryati, Sani; Makarim, Siti Amirah (Jurnal Pengabdian Kepada Masyarakat Multi Disiplin, 2025)
This study explores the implementation of the Experiential Learning Model in entrepreneurship education at SMA Serba Bakti. Using a qualitative approach, the research focuses on students’ understanding of entrepreneurial concepts, their level of participation in experience-based learning, their perceptions of the model’s effectiveness, and the development of entrepreneurial skills. Data were collected through participatory observation and in-depth interviews with students involved in entrepreneurship extracurricular activities. The findings indicate that the experiential learning model is effective in enhancing students’ comprehension of entrepreneurship, encouraging active engagement in the learning process, and strengthening practical skills in managing small businesses. These results highlight the importance of integrating experience-based learning approaches into the curriculum to better prepare students for the increasingly complex demands of the global job market.